2017
DOI: 10.5194/acp-17-10109-2017
|View full text |Cite
|
Sign up to set email alerts
|

Projected changes in haze pollution potential in China: an ensemble of regional climate model simulations

Abstract: Abstract. Based on the dynamic downscaling by the regional climate model RegCM4 from three CMIP5 global models under the historical and the RCP4.5 simulations, this article evaluated the performance of the RegCM4 downscaling simulations on the air environment carrying capacity (AEC) and weak ventilation days (WVDs) in China, which are applied to measure haze pollution potential. Their changes during the middle and the end of the 21st century were also projected. The evaluations show that the RegCM4 downscaling… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
40
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 59 publications
(43 citation statements)
references
References 44 publications
3
40
0
Order By: Relevance
“…If there is no change in aerosol emission in future, increased stagnation days and decreased light precipitation days associated with global warming would also cause an increase in air pollution days in eastern China (Chen et al, 2019). Regional climate model simulations under the RCP4.5 scenario showed that the air environment carrying capacity, a combined metric measuring the capacity of the atmosphere to transport and dilute pollutants, tends to decrease in the 21 st century across China (Han et al, 2017).…”
Section: Projections Based On Coupled Model Intercomparison Project Pmentioning
confidence: 99%
“…If there is no change in aerosol emission in future, increased stagnation days and decreased light precipitation days associated with global warming would also cause an increase in air pollution days in eastern China (Chen et al, 2019). Regional climate model simulations under the RCP4.5 scenario showed that the air environment carrying capacity, a combined metric measuring the capacity of the atmosphere to transport and dilute pollutants, tends to decrease in the 21 st century across China (Han et al, 2017).…”
Section: Projections Based On Coupled Model Intercomparison Project Pmentioning
confidence: 99%
“…Following the international Coordinated Regional Climate Downscaling Experiment (CORDEX)-East Asia phase II (Giorgi et al, 2009), the region for the downscaling simulations covers the whole China and the adjacent areas (Figure 1 (a)). The physical parameterization schemes employed are the same as that described in the studies of Gao et al (2016Gao et al ( , 2017 and Han et al (2017).…”
Section: Model Simulations and Datamentioning
confidence: 99%
“…The local meteorological conditions found to be associated with haze formation in Beijing include low wind speeds, high humidity content of air and low intensity of solar radiation 18,[23][24][25] . Climate warming arguably influences weather conditions in such a way that the likelihood of winter haze episodes in Beijing has already increased, and is likely to increase further in the future 12,[26][27][28][29] .…”
Section: Introductionmentioning
confidence: 99%